Peritoneal dialysis–related peritonitis with an unexpected micro-organism: enterococcus hirae - (:unkn) unknown (My University, 2017)
0

Enterococcus Hirae is a gram-positive, facultative, anaerobic bacterium which is usually a zoonotic pathogen rarely isolated from human infections. There are no published reports describing continuous ambulatory peritoneal dialysis (CAPD) related- peritonitis with Enterococcus Hirae in the literature. With the following report, we describe the case of peritoneal dialysis (PD)-related peritonitis due to Enterococcus Hirae
Keywords: Genel ve Dahili Tıp